Properties of magnetron hydroxyapatite coatings deposited on oxidized substrates - Starikov, V. V.; Kostuchenko, A. V.; Starikova, S. L.; Mamalis, A. G.; Lavrynenko, S. N. (Collegium Basilea & AMSI, 2016)
Hydroxyapatite (HA) coating were formed on oxidized niobium surfaces by the highfrequency magnetron sputtering method using hydroxyapatite and tricalcium phosphate targets. The structure, substructure and mechanical properties of the Nb–Nb2O5–HA system were investigated by X-ray diffraction, atomic force microscopy and nanoindentation and the stress state was assessed. The synthesized hydroxyapatite film had the following characteristics: thermal expansion coefficient 10–5 K–1; modulus of elasticity 120 GPa; adhesive strength not less than 0.45 kg/mm2; density 2900 kg/m3. The stress magnitude in the metal oxide substrate was from 11 to 14 MPa after hydroxyapatite film deposition.
Keywords: elasticity modulus; hydroxyapatite; magnetron sputtering; nanohardness; macrostresses; oxide